Penerapan Metode VIKOR pada Pengambilan Keputusan Seleksi Calon Penerima Beasiswa Bidikmisi Universitas Terbuka - Suniantara, I Ketut Putu; Suwardika, Gede (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2018)
The selection process of bidikmisi scholarship involves many requirements as a criterion, thus requiring completion decisions supporters with multi-criteria. One of the decision support concept with multi-citeria is VIKOR Method. The basic concept of the VIKOR Method is to determine the rank of available samples by looking at the results of utility values, regrets and distance solutions as the best alternative of each sample by weighting criteria from the Analytic Hierarchy Process Method. This research purpose is to apply the VIKOR method in selecting the recipients of bidikmisi scholarship by considering various criteria that have been determined. The results shows that the VIKOR Method can be used to assist the selection process and determine the right scholarship recipients. At the VIKOR Method, each weight that are involved shows the result rank value, so it can be used as a compromise solution in dealing with multicriteria problems.